An efficient organic–inorganic hybrid hole injection layer for organic light-emitting diodes by aqueous solution doping1. Issue 24 (28th June 2015) - Deng, Ya-Li; Xie, Yue-Min; Zhang, Lei; Wang, Zhao-Kui; Liao, Liang-Sheng
<x xml:space="preserve">Abstract</x> An efficient anode interfacial layer, MoO3 doped TS-CuPc, in OLEDs through an environmentally-friendly fabrication process is developed.